Correlation of bone fragments reposition and related parameters in thoracolumbar burst fractures patients - Dai, Jianhui (Int J Clin Exp Med, 2015)
The aim of this study is to determine if thoracolumbar vertebral body collapse or canal compromise (CC) is associated with reposition of bone fragment. We retrospective review medical charts of patients with thoracolumbar burst fractures from July 2010 to September 2013. The fractures were classified according to the Arbeit Fuer Osteoosynthese (AO) classification system. Neurological status was classified according to American Spinal Injury Association (ASIA). Patients were divided into two groups (reposition group and non-reposition group) according to whether the bone fragments were reposition or non-reposition after surgery. Mimics measured mid-sagittal canal diameter (MSD), transverse canal diameter (TCD), local kyphosis (LK) and calculated anterior vertebral body compression ratio (AVBCR), middle vertebral body compression ratio (MVBCR), posterior vertebral body compression ratio (PVBCR), and mid-sagittal canal diameter compression ratio (MSDCR) on the preoperative CT image. The results indicated that 55 patients were included in the study. There are 35 patients with reposition of bone fragment and 20 patients with non-reposition of bone fragment after surgery. There were significant difference on MSD (t = 3.258, P = 0.002), TCD (t = 2.197, P = 0.032), AVBCR (t = -2.063, P = 0.044), MVBCR (t = -2.526, P = 0.015), PVBCR (t = -2.211, P = 0.031), MSDCR (t = -4.975, P = 0.000) between two groups before surgery. There was a significant correlation between reposition of bone fragment and AO classification (OR = 5.251, P = 0.022), and MSDCR (OR = 7.366, P = 0.007). There was no significant correlation between reposition and AVBCR, MVBCR, PVBCR, LK, MSD and TCD. In conclusion, this study indicates that AO classification and MSDCR are predictors of reposition of bone fragment.